Hermeticity of electronic packages - Greenhouse, Hal (Materials science and process technology series., 2000)
Provides background and problem-solving examples applicable to package designers, package users, reliability engineers, and those who measure and evaluate the integrity of packages to apply this knowledge to solving their specific challenges. Attempts to answer the following questions: how do you define the goodness of the seal? how is that seal measured? how does the integrity of the seal effect circuit reliability? Includes more than 100 application-specific problems and their solutions.